Fracture Patterns and Comminution Zones in OTA/AO 34C Type Patellar Fractures. Issue 5 (May 2020) - Misir, Abdulhamit; Kizkapan, Turan Bilge; Uzun, Erdal; Oguzkaya, Sinan; Cukurlu, Mustafa; Golgelioglu, Fatih
Abstract : Objectives: To characterize the fracture patterns and comminution zones for complete articular (OTA/AO 34C type) patellar fractures, using a computed tomography mapping technique. Methods: Eighty-three OTA/AO 34C type patellar fractures were included. Images of patellar fractures were superimposed on a coronal template of the patella, created from a healthy right knee, to identify fracture patterns and comminution zones. Results: Our analysis was based on 83 computed tomography images of patellar fractures, contributed by 69 male and 14 female patients (mean age, 52 years; range, 18–79 years), and included 13 type C1, 26 type C2 and 44 type C3 fractures. A transverse fracture, including both the medial and lateral facets, was the most common fracture pattern, identified in 92.8% of cases. In the C1 and C2 types, the fracture line affecting the medial and lateral joint surface was either transverse or oblique. In the C3 type, the transverse and vertical fracture line of the medial articular surface extended to the inferior pole of the patella, with transverse and oblique fractures lines on the lateral joint surface. In addition, a concentration of the fracture lines around the vertical ridge was observed. Conclusions: The patterns of fracture lines and comminution zones OTA/AO 34C type fractures were repeatable on the constructed maps. A transverse fracture line on the inferior pole which was observed in the C2 and C3 type fractures may be used for the modification of current classification systems to direct treatment.